3s2+9s-12=0

Factor 3 out of 3s2+9s-12.

Factor 3 out of 3s2.

3(s2)+9s-12=0

Factor 3 out of 9s.

3(s2)+3(3s)-12=0

Factor 3 out of -12.

3s2+3(3s)+3⋅-4=0

Factor 3 out of 3s2+3(3s).

3(s2+3s)+3⋅-4=0

Factor 3 out of 3(s2+3s)+3⋅-4.

3(s2+3s-4)=0

3(s2+3s-4)=0

Factor.

Factor s2+3s-4 using the AC method.

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -4 and whose sum is 3.

-1,4

Write the factored form using these integers.

3((s-1)(s+4))=0

3((s-1)(s+4))=0

Remove unnecessary parentheses.

3(s-1)(s+4)=0

3(s-1)(s+4)=0

3(s-1)(s+4)=0

Divide each term in 3(s-1)(s+4)=0 by 3.

3(s-1)(s+4)3=03

Simplify 3(s-1)(s+4)3.

Cancel the common factor of 3.

Cancel the common factor.

3(s-1)(s+4)3=03

Divide (s-1)(s+4) by 1.

(s-1)(s+4)=03

(s-1)(s+4)=03

Expand (s-1)(s+4) using the FOIL Method.

Apply the distributive property.

s(s+4)-1(s+4)=03

Apply the distributive property.

s⋅s+s⋅4-1(s+4)=03

Apply the distributive property.

s⋅s+s⋅4-1s-1⋅4=03

s⋅s+s⋅4-1s-1⋅4=03

Simplify and combine like terms.

Simplify each term.

Multiply s by s.

s2+s⋅4-1s-1⋅4=03

Move 4 to the left of s.

s2+4⋅s-1s-1⋅4=03

Rewrite -1s as -s.

s2+4s-s-1⋅4=03

Multiply -1 by 4.

s2+4s-s-4=03

s2+4s-s-4=03

Subtract s from 4s.

s2+3s-4=03

s2+3s-4=03

s2+3s-4=03

Divide 0 by 3.

s2+3s-4=0

s2+3s-4=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -4 and whose sum is 3.

-1,4

Write the factored form using these integers.

(s-1)(s+4)=0

(s-1)(s+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

s-1=0

s+4=0

Set the first factor equal to 0.

s-1=0

Add 1 to both sides of the equation.

s=1

s=1

Set the next factor equal to 0.

s+4=0

Subtract 4 from both sides of the equation.

s=-4

s=-4

The final solution is all the values that make (s-1)(s+4)=0 true.

s=1,-4

Solve for s 3s^2+9s-12=0